Letter from W. E. Du Bois of the United States Mint to James Curtis Booth - Du Bois, William E. (William Ewing) (1879)
Brief note headed "Q for the M & R" written by William Ewing Du Bois (1810-1881), Assistant Assayer of the United States Mint. The note alerts James Curtis Booth (1810-1888) that the "toughening" of bars will cost more than the one cent per ounce allowed.
Keywords: Booth, James Curtis, 1810-1888; United States Mint; Mint of the United States; Du Bois, William E. (William Ewing), 1810-1881